Կրթության կառավարման արդի հիմնահարցերը և զարգացման միտումները - Սաֆարյան, Նաիրա (Զանգակ հրատ.)
В статье представлен краткий обзор формирования и развития понятия «управление ». Даны основные характеристики трех исторически сформированных подходов изучения управления. Представлены основные положения и взгляды известных теоретиков относительно различных подходов к изучению управления, в частности, в области образования. Определены актуальные вопросы управления образованием и отмечены основные тенденции развития. This article presents a brief overview of formation and development of “management”. The general characteristics of historically formed three ways of management investigation are done. There are presented the basic states and opinions of prominent theorists about several ways of management investigation, especially, in educational sphere. Contemporary issues of education management and the general tendencies of management development are determined.
Keywords: Կրթության մենեջմենթ